Character-Based Inclusive Education Management at Senior High School: A Qualitative Case Study - Al-Karimah, Nur Fadhilah; Abdullah, Mudhofir; Mujahid, Imam (AL-ISHLAH: Jurnal Pendidikan, 2024)
The objective of this study is to comprehend the management of character-based inclusive education at Al Firdaus High School, an institution recognized nationally for maintaining its status as an inclusive school with a focus on instilling character-based Islamic values. Awarded the Inclusive Education Award by the Ministry of Education and Culture in 2012, Al Firdaus High School serves as a model inclusive school. This qualitative research employs a case study approach, categorized under descriptive research, and was conducted at SMA Al Firdaus Sukoharjo, gathering data through participant observation, structured interviews, and documentation. The research identified ten-character values integrated into five national characters: religious, nationalist, independent, mutual cooperation, and integrity. Specifically, the values of being balanced and reflective are encompassed within the religious character; caring within the nationalist character; knowledgeable, inquiry-driven, risk-taking, and communicative within the independent character; open-minded within mutual cooperation; and thinker and principled within integrity. The study highlights how Al Firdaus High School integrates Islamic character-based values into its inclusive education framework, promoting inclusivity and holistic student development. This integration reflects the school’s commitment to fostering a balanced, reflective, caring, knowledgeable, inquisitive, risk-taking, communicative, open-minded, thoughtful, and principled student body. As a national model, the school’s recognition and award for inclusive education underscore its successful management and implementation of these principles, providing valuable insights for other institutions aiming to develop inclusive education programs grounded in character-based values.